333 Leg compartment pressures in collegiate runners: a comparison of symptomatic and asymptomatic athletes. (3rd March 2020) - Miller, Timothy; Early, Nicholas; Kaeding, Christopher
Abstract : Background: Chronic exertional compartment syndrome (CECS) is an uncommon cause of leg pain in running athletes. Post-exercise compartment pressure measurements are an invasive test that many clinicians rely upon for making the diagnosis of CECS. Objective: The authors sought to determine if intracompartmental pressures in the anterior leg compartments of asymptomatic collegiate distance runners meet established criteria for diagnosis of exertional compartment syndrome and to compare these measurements with those of symptomatic athletes. Design: Thirty collegiate running athletes underwent 1-minute post-exercise compartment pressure measurements of bilateral anterior leg compartments. Each was asked to run for 15 minutes at a moderately intense pace and then underwent measurements performed at 1 minute post-exertion with a slit catheter manometer. Fifteen male and 15 female collegiate running athletes age 18–23 years (average 20.8 years) underwent post-exercise compartment pressure testing of the legs. The pressure measurements were then compared with those of 30 symptomatic age- and activity-matched control athletes. Setting: Collegiate (University) Athletics. Patients (or Participants): Collegiate Track and Field and Soccer (Football) Athletes. Interventions (or assessment of risk factors): Post-exercise leg compartment pressure testing with slit catheter pressure measurements. Main outcome measurements: Bilateral leg anterior muscular compartment pressures immediately following provocative exercise. Results: Measurements of leg compartment pressures performed at 1-minute post-exercise were indicative of exertional compartment syndrome in more than one-third of asymptomatic running athletes tested (11/30, 36.7%). Six male and 5 female runners demonstrated 1-minute post-exercise compartment pressure measurements >30 mmHg in at least one leg. Of these 11 athletes, 4 demonstrated positive measurements bilaterally (2 men, 2 women). Intracompartmental pressure measurements ranged from 16 mmHg to 88 mmHg. The range of pressure measurements were nearly identical in the symptomatic runners. Conclusions: Elevated intracompartmental pressures were prevalent in collegiate runners despite a lack of symptoms. Post-exercise compartment pressure measurements should be viewed as only an indicator of exertional compartment syndrome and should not be relied upon as a confirmatory test.